Allogeneic and Autologous Bone-Marrow Transplantation - Deeg, H. Joachim (1988)
The author of this paper presents an overview of the current status of bone marrow transplantation, including indications, pre-transplant considerations, the transplant procedure, acute and delayed transplant-related problems, results currently attainable, and a short discussion of possible future developments.